CNT@MnO2 composite ink toward a flexible 3D printed micro‐zinc‐ion battery. Issue 3 (1st February 2022) - Ren, Yujin; Meng, Fanbo; Zhang, Siwen; Ping, Bu; Li, Hui; Yin, Bosi; Ma, Tianyi
Abstract: Flexible energy storage devices have played a significant role in multiscenario applications, while flexible zinc‐ion batteries (ZIBs), as an essential branch, have developed rapidly in recent years. Three‐dimensional (3D) printing is an extremely advanced technology to design and modify the structure of batteries and provides unlimited possibilities for the diversified development of energy storage equipment. Herein, by utilizing 3D printing technology, carbon nanotube (CNT) is coated by MnO2 to form a flexible CNT@MnO2 ink as a cathode for flexible aqueous micro‐ZIBs for the first time and zinc powder ink is used as an anode due to its high flexibility and bendability. The Zn//CNT@MnO2 flexible battery shows a stable capacity of 63 μAh cm −2 at 0.4 mA cm −2 . When the battery is bent in different states, the maximum capacity loss compared with the initial value is only 2.72%, indicating its stability. This study shows the potential of 3D printing technology in the development of flexible manganese‐based ZIBs. Abstract : Three‐dimensional (3D) printing is an extremely advanced technology to design and modify the structure of batteries, which provides unlimited possibilities for the diversified development of energy storage equipment. Herein, by utilizing 3D printing technology, flexible MnO2 @CNT ink is designed as a cathode for flexible aqueous micro‐zinc‐ion batteries (micro‐ZIBs) for the first time and zinc powder ink is used as an anode due to its high flexibility and bendability. The Zn/MnO2 @CNT flexible battery shows a stable capacity of 63 μAh cm −2 at 0.4 mA cm −2 . When the battery is bent in different states, the maximum capacity loss compared with the initial value is only 2.72%, indicating its stability. This study shows the potential of 3D printing technology in the development of flexible manganese‐based ZIBs.